Why We Do Not Evolve Software? Analysis of Evolutionary Algorithms. (November 2018) - Yampolskiy, Roman V
In this article, we review the state-of-the-art results in evolutionary computation and observe that we do not evolve nontrivial software from scratch and with no human intervention. A number of possible explanations are considered, but we conclude that computational complexity of the problem prevents it from being solved as currently attempted. A detailed analysis of necessary and available computational resources is provided to support our findings.